3D bioprinting of miniaturized tissues embedded in self-assembled nanoparticle-based fibrillar platforms - Bakht, Syeda M. (2021)
The creation of microphysiological systems like tissue and organ-on-chip for in vitro modeling of human physiology and diseases is gathering increasing interest. However, the platforms used to build these systems have limitations concerning implementation, automation, and cost-effectiveness. Moreover, their typical plastic-based housing materials are poor recreations of native tissue extracellular matrix (ECM) and barriers. Here, the controlled self-assembly of plant-derived cellulose nanocrystals (CNC) is combined with the concept of 3D bioprinting in suspension baths for the direct biofabrication of microphysiological systems embedded within an ECM mimetic fibrillar support material. The developed support CNC fluid gel allows exceptionally high-resolution bioprinting of 3D constructs with arbitrary geometries and low restrictions of bioink choice. The further induction of CNC self-assembly with biocompatible calcium ions results in a transparent biomimetic nanoscaled fibrillar matrix that allows hosting different compartmentalized cell types and perfusable channels, has tailored permeability for biomacromolecules diffusion and cellular crosstalk, and holds structural stability to support long-term in vitro cell maturation. In summary, this xeno-free nanoscale CNC fibrillar matrix allows the biofabrication of hierarchical living constructs, opening new opportunities not only for developing physiologically relevant 3D in vitro models but also for a wide range of applications in regenerative medicine.